Predicting Malignancy and Invasiveness of Pulmonary Subsolid Nodules on CT Images Using Deep Learning - Shen, Tianle; Hou, Runping; Ye, Xiaodan; Li, Xiaoyang; Xiong, Junfeng; Zhang, Qin; Zhang, Chenchen; Cai, Xuwei; Yu, Wen; Zhao, Jun; Fu, Xiaolong (Frontiers in Oncology, 2021)
Background: To develop and validate a deep learning-based model on CT images for the malignancy and invasiveness prediction of pulmonary subsolid nodules (SSNs). Materials and methods: This study retrospectively collected patients with pulmonary SSNs treated by surgery in our hospital from 2012 to 2018. Postoperative pathology was used as the diagnostic reference standard. Three-dimensional convolutional neural network (3D CNN) models were constructed using preoperative CT images to predict the malignancy and invasiveness of SSNs. Then, an observer reader study conducted by two thoracic radiologists was used to compare with the CNN model. The diagnostic power of the models was evaluated with receiver operating characteristic curve (ROC) analysis. Results: 2614 patients were finally included and randomly divided for training (60.9%), validation (19.1%) and testing (20%). For the benign and malignant classification, the best 3D CNN model achieved a satisfactory AUC of 0.913 (95% CI: 0.885-0.940), sensitivity of 86.1% and specificity of 83.8% at the optimal decision point, which outperformed all observer readers’ performance (AUC: 0.846±0.031). For pre-invasive and invasive classification of malignant SSNs, the 3D CNN also achieved satisfactory AUC of 0.908 (95% CI: 0.877-0.939), sensitivity of 87.4% and specificity of 80.8%. Conclusion: The deep learning model showed its potential to accurately identify the malignancy and invasiveness of SSNs and thus can help surgeons to make treatment decisions.